Teachers’ Instructional Supervision: Its Influence on Students’ Conceptual Understanding In The Language of Mathematics - Travero, Arnel; Berico, Ariel M (Universitas Galuh, 2025)
This study aims to examine the influence of teachers’ instructional supervision on students’ conceptual understanding in the language of mathematics. Specifically, it seeks to determine the relationship between instructional supervision components—organizational skills, goal setting, environment structuring, and help-seeking—and the conceptual understanding of 433 second-year Bachelor of Elementary Education (BEED) students at a community college in Bukidnon, Philippines. A descriptive-correlational research design was employed. Data were collected using two validated survey instruments: a 65-item adapted conceptual understanding test, and a 23-item instructional supervision questionnaire modified, both of which demonstrated acceptable reliability. Data were analyzed using descriptive statistics, Pearson correlation, and regression analysis. Despite generally positive perceptions of instructional supervision, students showed low levels of conceptual understanding. Statistically significant relationships were found between conceptual understanding and two supervision components: environment structuring (p = 0.001) and help-seeking (p = 0.002). Further, regression analysis identified environment structuring as a significant predictor of conceptual understanding (F = 3.876, p = 0.004). The findings suggest that instructional supervision, particularly in structuring learning environments and promoting help-seeking behavior, plays a crucial role in enhancing students’ grasp of mathematical concepts. The study recommends that teachers and school administrators develop strategies that strengthen these areas to improve mathematics learning outcomes.